1999
DOI: 10.1002/(sici)1097-0215(19990924)83:1<135::aid-ijc23>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Inverse regulation of neuronal cellular adhesion molecule (NCAM) by IFN-? in melanoma cell cultures established from CNS lesions

Abstract: In advanced stages of malignant melanoma (MM), metastases to the CNS are frequently observed. Few results are available on trophic factors and immunological features involved in the process of invasion and adhesion of circulating metastatic cells into the CNS. A direct comparison of remote metastases found in different locations of the same patient might help to identify such properties. For this purpose, we screened a panel of MM cell cultures, which had been established from patients with surgically removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In contrast, the down-regulation of NCAM was observed in the development of colon cancer and some of myeloma (12,13) and all neuroblastoma (14), suggesting that the role of NCAM on tumor progression is largely dependent on tumor types. In melanoma, the earlier studies demonstrated that melanoma from central nervous system (CNS) metastases and non-CNS-derived metastases exhibit distinct levels of NCAM (15) and high expression of NCAM was detected in aggressive metastasizing uveal melanoma (16). In addition, we also found that NCAM facilitates the cellular invasion and metastasis in a recent study (17).…”
supporting
confidence: 49%
“…In contrast, the down-regulation of NCAM was observed in the development of colon cancer and some of myeloma (12,13) and all neuroblastoma (14), suggesting that the role of NCAM on tumor progression is largely dependent on tumor types. In melanoma, the earlier studies demonstrated that melanoma from central nervous system (CNS) metastases and non-CNS-derived metastases exhibit distinct levels of NCAM (15) and high expression of NCAM was detected in aggressive metastasizing uveal melanoma (16). In addition, we also found that NCAM facilitates the cellular invasion and metastasis in a recent study (17).…”
supporting
confidence: 49%
“…104 Furthermore, in melanoma cell lines derived from central nervous system metastases, NCAM is constitutively expressed. 105 Despite these observations and the potential connection to PNI in other malignancies, to the best of our knowledge, we are not aware of any study that has investigated NCAM's relationship to PNI in melanoma. Enhanced expression of NCAM in DMs, in conjunction with studies demonstrating correlations with PNI in SCCs and pancreatic cancers suggest that such studies may be fruitful.…”
Section: Other Potential Players: a Role For Ncam And Cxcr4?mentioning
confidence: 97%
“…Additionally, in vitro studies in melanoma cell lines have found expression of NCAM to be linked with secretion of MMP-2 and therefore enhanced invasiveness (Shi et al, 2011). Furthermore, in melanoma cell lines derived from central nervous system metastases, NCAM is constitutively expressed (Geertsen, Zenklusen, Kamarashev, Burg, & Dummer, 1999). Despite these observations and the potential connection to PNI in other malignancies, to the best of our knowledge, we are not aware of any study that has investigated NCAM's relationship to PNI in melanoma.…”
Section: Other Potential Players: Ncam and Cxcr4mentioning
confidence: 98%